KESETARAAN DAN KESERASIAN GENDER DALAM AL-QURAN - Siti Alfiatun Hasanah; Lukman Hakim Husnan (JIA (Jurnal Ilmu Agama), 2022)
The narrative about gender justice is dominated by the notion of gender equality. In the interpretation of the Koran, this has serious implications, including forcing the application of the method of "hermeneutics of suspicion", which in addition to bringing down the spirits of classical commentators (due to allegations of gender bias), but more than that it also undermines the sacredity of the Holy Koran. Written using worldview theory, this article presents and at the same time discusses alternative discourse for the assumption of gender equality, namely the idea of ​​gender harmony, which is actually an Islamic original narrative in responding to demands and / or guidance on gender justice.